Study of Technological Surveillance in Electric River Mobility for Cargo Transport on the Atrato River, Colombia - Zapata-Campo, Edinson; Rico-Carrillo, Katherine; Salazar-Arrieta, Fernando; Paipa-Sanabria, Edwin; Zapata-Cortes, Julian (Journal of Technology Innovations in Renewable Energy, 2024)
Electric mobility is a modality that has been implemented worldwide, however, the importance of the use of this type of environmentally friendly energy occupies a space at the top of this list that to provide solutions in this regard, the National Navy through the Corporation of science and technology for the development of the maritime and river naval industry (COTECMAR), As part of the project executor, Design of an Eco-friendly electric vessel (ECOTEA) for cargo transport on the Atrato River, Colombia, the research project was carried out, technological surveillance study to know the advances and state of development in electric river mobility for cargo transport as an applicable alternative in the Atrato River, in Colombia, as part of the Energy Transformation for Environmentally Friendly Eco Transport, carried out by institutions recognized by the Ministry of Science, Technology and Innovation, such as: the National University, Center for Research and Administrative Planning (CEIPA), Technological University of Chocó, University of Cartagena, the Institute of Environmental Research of Chocó and the Colombian Institute of Technical Standards and Certifications (ICONTEC), as co-executors of the project. The justification for this research project is based on the UN’s Sustainable Development Goals, specifically number 7, which seeks to guarantee access to safe, sustainable and modern energy, as well as the commitments acquired by Colombia through the river master plan, which has as its main objective to obtain a more competitive river system. clean, safe and beneficial for national development, with the design and construction of an ecologically friendly vessel (ECOTEA), specifically on the Atrato River, benefiting an estimated population of 370 thousand people in the energy transition program. The development of the research was descriptive with a qualitative approach because it contributed to the planning of the roadmap to be drawn.